SGLT-2 inhibitors and the risk of infections: a systematic review and meta-analysis of randomized controlled trials - Puckrin, Robert; Saltiel, Marie-Philippe; Reynier, Pauline; Azoulay, Laurent; Yu, Oriana H. Y.; Filion, Kristian B. (Acta diabetologica, 2018)
Aims There is concern about the infection-related safety profile of sodium–glucose co-transporter 2 (SGLT-2) inhibitors. We aimed to determine the effect of SGLT-2 inhibitors on genitourinary and other infections via systematic review and meta-analysis of randomized controlled trials (RCTs). Methods We conducted a systematic search of Medline, EMBASE, Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov to identify double-blinded RCTs enrolling ≥ 50 patients with type 2 diabetes which compared an SGLT-2 inhibitor to placebo or active comparator. Two independent reviewers extracted data and appraised study quality. Data were pooled using random-effects models. Results Eighty-six RCTs enrolling 50,880 patients were included. SGLT-2 inhibitors increased the risk of genital infections compared to placebo (relative risk [RR] 3.37, 95% CI 2.89–3.93, I 2 0%) and active comparator (RR 3.89, 95% CI 3.14–4.82, I 2 0.3%). The risk of urinary tract infection (UTI) was not increased with SGLT-2 inhibitors compared to placebo (RR 1.03, 95% CI 0.96–1.11, I 2 0%) or active comparator (RR 1.08, 95% CI 0.93–1.25, I 2 22%). In drug-specific analyses, only dapagliflozin 10 mg daily was associated with a significantly increased risk of UTI compared to placebo (RR 1.33, 95% CI 1.10–1.61, I 2 0%). SGLT-2 inhibitors were associated with a reduced risk of gastroenteritis (RR 0.38, 95% CI 0.20–0.72, I 2 0%) but did not affect the risk of respiratory tract infections. Conclusions/interpretation SGLT-2 inhibitors are associated with an increased risk of genital tract infections. Although there is no association overall between SGLT-2 inhibitors and UTI, higher doses of dapagliflozin are associated with an increased risk.